Performance Enhancement of 100WP Monocrystalline Solar Panel using Mirror Reflectors - Dionova, Brainvendra Widi; Rahmanda, Ibnu Dwi; Putri, Arisa Olivia; Eteruddin, Hamzah; Pratama, Legenda Prameswono; Hendrawati, Dwiana; Abdulrazaq, Mohammed N. (Jurnal Edukasi Elektro, 2025)
This research analyzes how the reflection of sunlight intensity affects the power generated by a 100WP monocrystalline solar panel with the addition of various reflector tilt angles. An experimental method was used to conduct this analysis by comparing three tests: a solar panel without a reflector, with a 60° angled reflector, and with a 75° angled reflector. Data was collected at one-hour intervals from 09:00 to 16:00 WIB, measuring parameters such as temperature, intensity, voltage, current, and power. The results showed that the addition of a flat mirror reflector significantly improved the performance of the solar panel. With a 75° tilt angle, the total power generated was 373.32W, compared to the total power generated at 60° of 366.93W and without a reflector of 208.62W. The highest power peak was achieved at 13:00 WIB with the 75° reflector at 69.31W. This research demonstrates that a reflector tilt angle of 75° is the most optimal for increasing the efficiency of monocrystalline solar panels as it distributes sunlight more evenly across the panel surface. The recommendation for future research is the utilization of software-based simulations and IoT integration for real-time monitoring, to strengthen experimental data validation and expand the application of this technology at both industrial and household scales.